PERBANDINGAN HARAPAN KONSUMEN MERER SEPEDA MOTOR SUZUKI DAN HONDA DALAM ASPEK PRODUK, HARGA, SALURAN DISTRIBUSI DAN PROMOSI - J.E. Sutanto; Christian Yohandoyo (Journal of Management and Business, 2011)
Consumers' expectations are the cornerstones of consumer to make purchase decisions. In fact the level of someone's expectations can be assessed, can be measured, and can be affected. The purpose of this study is to determine whether there are differences between consumer expectation levels Suzuki and Honda motorcycles. The population of this study is the owner of Suzuki and Honda motorcycles. While sample is set at 97 respondents consisting of 71 Suzuki motorcycle owners and 26 owners of Honda motorcycles. The analysis technique used in this study is Manova. The results after using Manova analysis there are significant differences between Honda’s and Suzuki’s respondents at price variable, whereas in product, distribution channel, and promotion variables found no significant differences. The conclusion showed that there is the difference of level of consumer expectations Suzuki and Honda motorcycles in the price variable. The contribution on this research is Honda motorcycle dealers can increase sales by increasing of consumer expectations in product, pricing, distribution channels, and promotion.